SIMBOL BUDAYA MASYARAKAT JAWA DALAM KARYA SASTRA - Asrini, Hari Windu (Jurnal Bestari, 1992)
As other nations, Indonesians have many symbols. They live in thousands of islands that have specific culture. Javanese is one of them. The great part of Indonesians live in it. They have many symbols that denoted their characteristic culture. One of the common and specific characters of Javanese can be tracered to Linus Suryadi's monumental roman.